2014
DOI: 10.1007/s11010-014-2285-y
|View full text |Cite
|
Sign up to set email alerts
|

CXCL13-CXCR5 axis promotes the growth and invasion of colon cancer cells via PI3K/AKT pathway

Abstract: CXCL13, an inflammatory factor in the microenvironment, plays a vital role in the progression of inflammatory diseases and tumors. CXCL13 and its receptor CXCR5 have been reported to be associated with poor prognosis of advanced colon cancer. However, the molecular mechanisms of CXCL13-CXCR5 axis in colon cancer remain elusive. The aim of this study was to investigate the role of CXCR5-CXCL13 axis in the growth and invasion of colon cancer cells. Our results showed that CXCL13 promoted the growth, migration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 26 publications
(28 reference statements)
1
54
0
Order By: Relevance
“…Among various chemokines, C-X-C motif ligand 13 (CXCL13, also named as B-cell attracting chemokine 1 (BCA-1)) is thought to play an important pro-tumor role in colon, prostate, and breast cancers through the interaction with its receptor, the C-X-C chemokine receptor 5 (CXCR5) [ 12 - 14 ]. In particular, a recent in vitro study with colorectal cancer cell lines reported the interaction of CXCL13 with CXCR5 activated the phosphatidylinositol-3 kinase (PI3K)/AKT pathway leading to migration and invasion of cancer cells [ 15 ]. In NHL, a recent prospective study of inflammatory markers demonstrated a significant association of serum CXCL13 with the risk of lymphoma supporting its role in the lymphoma development [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among various chemokines, C-X-C motif ligand 13 (CXCL13, also named as B-cell attracting chemokine 1 (BCA-1)) is thought to play an important pro-tumor role in colon, prostate, and breast cancers through the interaction with its receptor, the C-X-C chemokine receptor 5 (CXCR5) [ 12 - 14 ]. In particular, a recent in vitro study with colorectal cancer cell lines reported the interaction of CXCL13 with CXCR5 activated the phosphatidylinositol-3 kinase (PI3K)/AKT pathway leading to migration and invasion of cancer cells [ 15 ]. In NHL, a recent prospective study of inflammatory markers demonstrated a significant association of serum CXCL13 with the risk of lymphoma supporting its role in the lymphoma development [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…CXCL-13, which expressed in lymphoid organs and some tumor tissues, has attracted a lot of attention for its important role in attracting tumor cells spreading to these sites and promoting bad clinical outcomes [17,27,28]. Zhu et al [29] study showed CXCL-13 promoted colon cancer cells growth and migration via activating the PI3K/AKT pathway. Furthermore, CXCL-13 promoted matrix metalloproteinase 13 expression and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The role of B-cells, and its supporting cell types in immunosurveillance is complex and dichotomous. On one hand, animal models studies suggest participation in proliferation and metastasis by promoting chronic inflammation, and suppressing antitumor responses [38], while on the other hand, promote long term survival leading to increased intratumor densities of tumor infiltrating immune cells suppressing tumorigenesis [39]. MS4A1 (CD20, tumor infiltrating B-cell marker), and BACH2 (a well-known transcriptional regulator of B and TFH cells), two genes previously implicated in contributing to immune landscape differences between RSCC and LSCC [39], are more predominantly suppressed within distal tumors.…”
Section: Suppressed Immune Signaling Predominates Left-sided Colon Tumentioning
confidence: 99%